2010
DOI: 10.1088/0022-3727/43/27/275202
|View full text |Cite
|
Sign up to set email alerts
|

Discharge characteristics of a nano-sized electrode with aligned carbon nanotubes grown on a tungsten whisker tip under various gas conditions

Abstract: Vertically aligned multiwalled carbon nanotubes were grown on a tungsten (W) tip by thermal chemical vapor deposition (CVD), applying a negative biasing voltage to the W tip in a pin-plate electrodes configuration. The carbon nanotube(CNT) electrodes, due to their nano-sized tip radii, create very high electric fields, and reduce significantly the breakdown voltage. Comparing the CNTs-grown W tip electrode to the W tip electrode, the ignition voltage for the former case decreased from 230 V to 181 V, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The increased discharge current with the reverse polarity is also consistent with the results reported in Ref. 18.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The increased discharge current with the reverse polarity is also consistent with the results reported in Ref. 18.…”
Section: Resultssupporting
confidence: 92%
“…Another study shows that discharge currents (in a corona phase) with CNT-forest cathodes are 6-7Â larger than those with tungsten cathodes. 18 The discharge current densities calculated from Fig. 2(a) at 10 V for the normal and reverse polarities (assuming that the current is uniformly distributed over the bottom surface of the 93-lm-diameter electrode) are 10.3 A/cm 2 and 29.5 A/cm 2 , respectively, giving a 2.86Â increase in the discharge current when the reverse polarity or the CNT-forest cathode is used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their extremely small tips with nanometer radii and high aspect ratios, CNTs are known to have excellent electron field-emission properties compared to the tungsten tip (a typical material used as EDM tool) [12]. It has recently been found that reverse-polarity EDM of CNT forests that are defined as the cathode in air ambient enhances the patterning tolerances and quality with decreased discharge energies [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports with different anode-cathode configurations such as planer electrodes [8], flat and point electrode [9], wire electrode and plate electrode [10], rod electrodes [11], co-planer electrodes [12], and many more. Above said configurations are mostly the combinations of metals.…”
Section: Introductionmentioning
confidence: 99%